Content marketing strategy (case study: gogh!) - Kotaro, Hans; Fathnur Ahmad, Nazmi (The Indonesian Journal of Business Administration, 2018)
Abstract – During this contemporary period (2017), the Internet has become one of the major supporting factors that substantiate business across the globe. The growth of E-commerce or online-based business is impacted greatly by the increasing number of Internet users. According to a survey conducted by the Indonesian Central Bureau of Statistics (BPS) within the period of 10 years; E-Commerce growth has increased by 17 percent, which is a total increase of 26.2 million E-commerce businesses in the span of 2006 until 2016. Even though more companies have turned to digital marketing on 2017, there are still challenges ahead. According to Iwan Setiawan and Savitry Yosanova on the book "New Content Marketing" (2016), people are not directly consumed by advertisement due to the three global shifts that occurred within this period. The first shift is the conversion from 'vertical' to 'horizontal.' In this shift, the marketers should not position themselves above the customers. Customers are asking to be on the same level as marketers. They want the freedom to decide what they want to say and do. The second shift is the conversion from 'exclusive' to 'inclusive.' These shifts and changes have successfully shaped an era of New Wave Marketing, whereas promotions are eventually turned into conversations. The occurrence of this conversation process should be done by methods of 'storytelling'. Along with the story, the prospective consumers will engage and generate conversation about the brand with other prospective customers. The use of Content Marketing tactics can eliminate distance and shape a friendlier, more relatable image with the customers. Content Marketing have different concepts in contrast to conventional advertising, as it conveys what the customer want to hear. When content marketing speaks, the concept of customer centrism is preferred. The brand prioritizes on what the customers preferred to to hear, and creativity takes precedence as the key (Setiawan and Yosanova, 2016).'Gogh!' is a lifestyle brand that provides affordable designers apparel. The brand caters to its interpretation of contemporary culture and produce sustainable fashion with a flair of Pop Art.  The company was founded in 2015, but officially run in 2016. The researcher used two types of methodology; quantitative and qualitative research, then the researcher use SWOT and PESTLE to analyze the business.  The next process is determine the objective, Interviewing the customer, target mapping, creating content in content ideation process, creating content in content ideation, distributing the content in content distribution process and evaluating the result in content marketing evaluation. Keywords:  Gogh, geek, popculture, marketing, content marketing